Foliar application of urea during bloom increases fruit size in 'Williams' pears - Sanchez, Enrique Eduardo; Curetti, Mariela; Sugar, David (ISHS, 2025)
Trabajo presentado al X International Pear Symposium, Peniche (Portugal), mayo de 2007